COVID-19 and Spontaneous Resolution of Lumbar Disk Prolapse: A Retrospective Cohort Study of Patients Awaiting Microdiscectomy - Hutton, Dana; Mohamed, Belal; Mehmood, Khalid; Magro, James; Shekhar, Himanshu; Solth, Anna; Pulhorn, Heinke; Bennett, David; Okasha, Mohamed (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Between individual patients with lumbar disk prolapse (LDP), the natural course of disease is significantly variable. Spontaneous resolution is reported to occur in up to 70% of cases. However, we currently cannot predict for whom and when this will occur. Neurosurgical intervention is indicated for LDP patients with nontolerable pain after at least 8 to 12 weeks of conservative management, or significant neurologic deficit. Channeling essential resources in the National Health Service (NHS) to fight the COVID-19 pandemic led to the postponement of most elective operations, including microdiskectomy. This left many LDP patients previously considered to be surgical candidates with conservative-only options in the interim. To our knowledge, we are the first center to report the specific impact of the peri- and postpandemic period on waiting list times, delayed elective microdiskectomy, and the incidence of spontaneous LDP resolution.Methods Retrospective case series of a prospectively collected electronic departmental database identified LDP patients who would have been impacted by the COVID-19 pandemic at some point in their care pathway (March 2020–February 2022). Further information was obtained from electronic patient records.Results In total, 139 LDP patients were listed for elective microdiskectomy at the time of postponement of elective surgery. Over a third of LDP patients (n = 47, 33.8%), in shared decision with the responsible neurosurgeon, had their rescheduled microdiskectomy canceled due to clinical improvement (14.1%), radiologic regression (6.5%), or both (12.2%).Conclusion Our single-center retrospective analysis revealed that for over a third of LDP patients, the prolonged postpandemic waiting list times for elective microdiskectomy resulted in their surgery not taking place either due to spontaneous clinical improvement or proven radiologic regression. Considering this, a prolonged conservative approach to LDP may be appropriate in some patients, allowing time for natural resolution, while avoiding perioperative risks.
Keywords: spontaneous resolution; disk prolapse; microdiskectomy; coronavirus-19; pandemic